Establishment of a Necroptosis Related Genes Signature to Predict Prognosis and Therapeutic Response in Colon Cancer - Wang, Yuan; Huang, Yongbiao; Li, Chunya; Wang, Xi; Yang, Mu; Xu, Duo; Liu, Bo; Yuan, Xianglin (Frontiers in Cell and Developmental Biology, 2022)
Necroptosis, as a form of programmed cell death, is involved in many physiological and pathological processes. However, its role in cancer progression and therapeutic response remains controversial. Colon cancer is one of the leading causes of cancer death and patients’ response to immune checkpoint blockade vary to a large degree. In this study, we investigated necroptosis related genes (NRGs) alterations in colon cancer by integrating multi-omics data. Colon cancer patients were classified into two heterogeneous subtypes with distinct clinical and molecular features based on NRGs. After finding differentially expressed genes and lasso regression, a prognostic model based on 4 necroptosis signature genes was constructed. The necroptosis signature was also a good predictor in the field of chemotherapy and immunotherapy in colon cancer. Altogether, this study illustrates the relationship between necroptosis and colon cancer, and establishes a novel scoring method to predict prognosis and therapeutic response in colon cancer patients.